Odpowiedzi

  • Użytkownik Zadane
2010-03-29T14:18:30+02:00
A) 2(5a-3)-a-4(3a-2)=0
10a-6-a-12a+8=0
-3a+2=0
-3a=-2 /:(-3)
a=2/3

B)2b-(1-b)=11-b
2b-1+b=11-b
4b=12
b=3

C) ²/₅(x-2)=x+4
2/5x- 4/5 = x+4
-3/5x=16/5
x=-16/3


D) 3y-2(y-1)-6
3y-2y+2-6=0
y=4


E) 3(3-5y)=90-5(3y-2)
9-15y=90-15y+10
0=91

sprzeczne ( o ile dobrze przepisałeś przykład)

F) ¼z+(z-6)=⅔(z-2)

1/4z+z-6=2/3z-4/3
7/12z=-4/3+6
z=8








11 4 11
2010-03-29T14:22:25+02:00
A) 2(5a-3)-a-4(3a-2)=0
10a - 6 - a - 12a + 8 = 0
-3a = 6 - 8
-3a = -2 / :(-3)
a = 2/3

B)2b-(1-b)=11-b
2b - 1 + b = 11 - b
2b + b + b = 11 + 1
4b = 12 /: 4
b = 3

C) ²/₅(x-2)=x+4
2/5x - 4/5 = x + 4
2/5x - x = 4 + 4/5
2/5x - 5/5x = 4 i 4/5
-3/5x = 24/5 /: (-3/5)
x = 24/5 x (-5/3)
x = -120/15
x = - 8

D) 3y-2(y-1)-6
3y - 2y + 2 - 6 = 0
y = 6 - 2
y = 4

E) 3(3-5y)=90-5(3y-2)
9 - 15y = 90 - 15y + 10
-15y + 15y = 90 + 10 - 9
0y = 109 równanie sprzeczne

F) ¼z+(z-6)=⅔(z-2)
1/4z + z - 6 = 2/3z - 4/3
1/4z + z - 2/3z = -4/3 + 6
3/12z + 12/12z - 8/12z = -4/3 + 18/3
7/12z = 14/3 /: (7/12)
z = 14/3 x 12/7
z = 168/21
z = 8
10 3 10